PERAN MOTIVASI BERWIRAUSAHA MEMODERASI PENGARUH PRAKERIN, TEACHING FACTORY, KREATIVITAS TERHADAP KETERAMPILAN BERWIRAUSAHA - M Fathur Rahman; Eka Fitriani; Kusumantoro Kusumantoro (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to investigate the effectiveness of apprenticeship, teaching factory, and creativity on entrepreneurship skills with entrepreneurship motivation as a moderating variable. This research is quantitative research. The population of this study were students of class XII BDP SMKN 1 Bawang. Methods of data collection using a questionnaire. Data analysis techniques used descriptive statistics and SEM-PLS analysis with the SmartPLS 4.0 analysis tool. The results of the study show that internship has a positive and significant effect on entrepreneurship skills. Teaching factory has a positive and significant effect on entrepreneurial skills. Creativity has a positive and significant effect on entrepreneurial skills. Entrepreneurial motivation cannot moderate the effect of apprenticeship on entrepreneurship skills. Entrepreneurial motivation cannot moderate the effect of teaching factory on entrepreneurship skills. Entrepreneurial motivation moderates the influence of creativity on entrepreneurial skills.